(untitled) (Reflection and Critique Law Magazine, 2022)
The presence of conflicts in various orders is inevitable life in society. The crime, for example, mirrors a social conflict that causes harm to the parties and breaks with the balance of intersubjective relations. Hence arises the right of the state to punish through the traditional penal system, based on the model of retributive justice. Currently, it is realized that this model has not responded to the satisfaction of the demands and objectives to which it is proposed. More often, there is a society immersed in numerous crimes, from those of minor offensive potential to the most violent crimes. From the above in these premises, there is an urgent need to rethink the current punitive model of criminal justice.Thus, the Restorative Justice emerges in this scenario, which proposes a new form of criminal intervention, with a view to reparation of damages and the rebalancing of social relations. Thus, restorative justice aims at the idealization of a more humane, legitimate and democratic criminal model, based on the protection of fundamental rights, as well as on the construction of a free and solidary society. The Brazilian conflict resolution system has several lenses through which possibilities and insertion of restorative practices are contemplated. There are in the Brazilian legal system some criminal institutes that have a new paradigm to adapt them to the precepts of Restorative Justice.